Smoking associated factors in students during their last year of higher education - Zuzulich Pavez, María Soledad; Cabieses Valdés, Báltica; Pedrals Gibbons, Nuria; Contreras Escudero, Lorena; Martínez Aldunate, Daniel; Muñoz Serrano, Mónica; Espinoza Sepúlveda, Manuel (Investigación y Educación en Enfermería, 2010)
Objective. To determine the risk factors associated to smoking in the last year of school in a Chilean university population. Methodology. Analytical, observational, transversal cut study. Stratified randomized sampling was conducted according to academic unit and year of career; the size of the sample was of 2045 students from four campuses of the catholic university of Chile. The information was collected with a self-applied questionnaire. A descriptive, bivariate and logistic regression analysis was made. Results. The average age was 20.4±1.6, 46% were males and 70.3% had a high socioeconomic status. 91% had started cigarette consumption before the age of 18. The smoking monthly prevalence was of 40.5%, 20% of the surveyed would be at risk of having diagnosis of smoking. A positive association was found between smoking during the last year of university and: age (p< 0.05), female sex (p< 0.001), socioeconomic status (p< 0.05) and parents drug consumption perception (p< 0.001). A negative association was found between smoking and religiosity (p< 0.001). Conclusion. In the studied university group it was found that the smoking problem requires special attention due to its magnitude and association to risk factors as age, female gender, socioeconomic status and a low religiosity.